Combined treatment of 3-hydroxypyridine-4-one derivatives and green tea extract to induce hepcidin expression in iron-overloaded β-thalassemic mice - Supranee Upanan (2018)
© 2015 Hainan Medical University. Objective: To evaluate the efficacy of deferiprone (DFP), 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one (CM1) or green tea extract (GTE) in enhancing expression of hepatic hepcidin1 (Hamp1) mRNA and relieving iron overload in β-globin knockout thalassemic mice. Methods: The β-globin knockout thalassemic mice were fed with a ferrocene-supplemented diet for 2 months and oral administration of deionized water, DFP (50 mg/kg), CM1 (50 mg/kg), GTE (50 mg epigallocatechin 3-gallate equivalent/kg), GTE along with DFP (50 mg/kg), and GTE along with CM1 (50 mg/kg) every day for 3 months. Levels of hepatic Hamp1 mRNA, plasma non-transferrin bound iron, plasma alanine aminotransferase activity and tissue iron content were dete rmined. Results: All chelation treatments could reduce plasma non-transferrin bound iron concentrations. Additionally, hepatic Hamp1 mRNA expression was significantly up-regulated in the mice in a GTE + DFP combined treatment, correlating with a decrease in the plasma alanine aminotransferase activity and tissue iron deposition. Conclusions: The GTE + DFP treatment could ameliorate iron overload and liver oxidative damage in non-transfusion dependent β-thalassemic mice, by chelating toxic iron in plasma and tissues, and increasing hepcidin expression to inhibit duodenal iron absorption and iron release from hepatocytes and macrophages in the spleen. There is probably an advantage in giving GTE with DFP when treating patients with iron overload.